The Issue of Acute Kidney Injury in Patients after Cardiac Surgery - D. G. Balakhnin; I. I. Chermnykh; A. A. Ivkin; D. V. Borisenko; E. V. Grigoryev (Вестник анестезиологии и реаниматологии, 2022)
Cardiac surgery associated acute kidney injury (CSA-AKI) is a common complication of cardiac surgery resulting from the patient's exposure to a complex combination of factors in the perioperative period. Current diagnostic criteria for AKI may underestimate the incidence of this complication due to certain specific features of cardiac surgery patients. The introduction of new diagnostic biomarkers of kidney injury into clinical practice has shown the prospective of identifying patients in the early stages of CSA-AKI development. Accurate and timely identification of patients at high risk of developing CSA-AKI can also allow performing comprehensive interventions to prevent it. When diagnosed, CSA-AKI management limited to symptomatic treatment.